PROFESSIONAL ENGLISH CONVERSATION TRAINING FOR THE FRONT OFFICE STAFF OF WYNDHAM HOTEL PALEMBANG - Wijaya, Beni; Zakaria, Zakaria; Darmaliana, Darmaliana; Kamilah, Athirah Putri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Effective communication is essential for success in the profitable hotel sector. In this line of work, communication is crucial to a seamless and productive exchange between hotel service personnel and guests. In today's competitive hotel industry, training in English communication skills offers several benefits, including increased productivity at work, enhanced customer satisfaction, and long-term success. This training initiative serves as a community service project that showcases the front office staff of Wyndham Hotel Palembang's proficiency in professional English conversation with customers. Interviews were conducted to assess participants' satisfaction with the training's content and methodology. The majority of participants expressed positive opinions about the training's methods and content, as indicated by the findings. The conclusions of this community service project raise awareness among employers, directors, and industry specialists about the need to reevaluate the approach and substance of hotel staff communication skills training. Further discussion was held regarding the implications of providing hotel front office staff with well-designed training in English conversation skills.